Peroneal artery pseudoaneurysm with arteriovenous fistula after calcaneal fracture surgery: a case report - Li, Yu-Long; Chen, Sheng; Ai, Yu; Zhang, Wei; Liu, Ji-Chao; Yang, Ya-Fan (Frontiers in Surgery, 2025)
BackgroundPeroneal artery injury following internal fixation of a calcaneal fracture is rare. The occurrence of a delayed pseudoaneurysm with an arteriovenous fistula after a peroneal artery injury is even rarer and has not been reported previously.Case summaryHerein, we report the case of a 65-year-old female patient with a calcaneal fracture (Sanders Type ⅢAB) who underwent an open reduction and internal fixation surgery through the tarsal sinus approach. Two months postoperatively, she experienced left foot pain. Physical examination revealed pulsation at the surgical site and a positive Branham sign, which was suggestive of a delayed pseudoaneurysm. Emergency digital subtraction angiography (DSA) examination was performed, and this revealed a pseudoaneurysm and arteriovenous fistula at the distal end of the peroneal artery. Therefore, the patient underwent transcatheter coil embolization of the peroneal artery and had good postoperative outcomes.ConclusionArterial injury should be suspected if massive hemorrhage occurs shortly after internal fixation for calcaneal fractures, and appropriate hemostatic measures should be promptly instituted. If unexplained pain and swelling develop along with a palpable pulse at the surgical site, a pseudoaneurysm should be suspected, and appropriate examinations should be promptly performed. Accurate diagnosis and prompt treatment are also crucial.